2021
DOI: 10.1186/s12868-021-00673-w
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement characteristics in male patients with deficit and non-deficit schizophrenia and their relationships with psychiatric symptoms and cognitive function

Abstract: Background The cognitive impairment pattern of deficit schizophrenia (DS) is centered on an impaired attention function. Previous studies have suggested that the exploratory eye movement (EEM) tests reflect attention deficits in patients with schizophrenia. However, no study has investigated the characteristics of eye movement in DS in the Chinese Han population. This study aimed to investigate the pattern of eye movement characteristics in DS patients and to examine whether eye movement charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…For instance, Bryant et al reported a significant difference in white matter neurometabolic signatures between DS and NDS patients using single-voxel magnetic resonance spectroscopy technology (48). Zhang et al found that DS patients had different eye movement characteristics than NDS patients (49). Moreover, some previous studies also provided evidence suggesting an association between the DS subtype of schizophrenia and gene polymorphisms, including dopamine D2 receptor and catechol-O-methyltransferase (COMT) genes (50, 51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bryant et al reported a significant difference in white matter neurometabolic signatures between DS and NDS patients using single-voxel magnetic resonance spectroscopy technology (48). Zhang et al found that DS patients had different eye movement characteristics than NDS patients (49). Moreover, some previous studies also provided evidence suggesting an association between the DS subtype of schizophrenia and gene polymorphisms, including dopamine D2 receptor and catechol-O-methyltransferase (COMT) genes (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. found that DS patients had different eye movement characteristics than NDS patients ( 49 ). Moreover, some previous studies also provided evidence suggesting an association between the DS subtype of schizophrenia and gene polymorphisms, including dopamine D2 receptor and catechol-O-methyltransferase (COMT) genes ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. (2021) reported lower NEF values in patients with schizophrenia compared to healthy controls, with a further reduction in patients with schizophrenia with pronounced negative symptoms ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear, however, whether these cognitive deficits are pervasive or more severe within certain specific domains. In this regard, one recent study utilizing eye movement analysis suggested that the major deficits were related to attention 41 , while another suggested that DS patients had significantly impaired overall cognitive abilities, possibly associated with chronic neuroinflammation 42 . While the true extent of cognitive deficits in DS remains uncertain, the current study supports more pervasive deficits, at least in patients with a long (several decade) disease history.…”
Section: Discussionmentioning
confidence: 99%